Modern Multi-Factor Analysis of Bond Portfolios Critical Implications for Hedging and Investing - Barone-Adesi, Giovanni; Carcano, Nicola (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Where institutions and individuals averagely invest the majority of their assets in money-market and fixed-income instruments, interest rate risk management could be seen as the single most important global financial issue. However, the majority of the key techniques used by most investors were developed several decades ago, and the advantages of multi-factor models are not fully recognised by many researchers and practitioners. This book provides clear and practical insight into bond portfolios and portfolio management through key empirical analysis. The authors use extensive sets of empirical data to describe the value potentially added by more recent techniques to manage interest rate risk relative to traditional techniques and to present empirical evidence of such an added value. Beginning with a description of the simplest models and moving on to the most complex, the authors offer key recommendations for the future of rate risk management.